The mitochondrial genome of the antarctic springtail Folsomotoma octooculata (Hexapoda; Collembola), and an update on the phylogeny of collembolan lineages based on mitogenomic data - CARAPELLI, ANTONIO; NARDI, FRANCESCO; FRATI, FRANCESCO; P. Convey (Entomologia, 2014)
This study provides the description of the complete mitochondrial genome of the Antarctic collembola Folsomotoma octooculata. Since mitogenomic data are extensively used for phylogenetic reconstruction, we also provide a phylogenetic reconstruction of the internal relationships of some collembola taxa using the complete mitochondrial DNA data available at present for this group. The complete mitochondrial genome sequence of F. octooculata has been obtained using standard amplification and sequencing methods for long DNA templates. Sequence data are analyzed using bayesian methods based on the analysis of nucleotide and amino acid sequences. The complete set of available mitochondrial DNA sequences for ten species of the group is also analyzed for the presence of lineage-specific gene order of the 37 encoded genes. The results of the phylogenetic analysis are compared with previous morphological and molecular analyses, showing some intriguing outcomes, such as the paraphyly of Entomobryomorpha, the derived position of Podura aquatica within Poduromorpha, and the sister group relationships between the single Symphypleona species available for comparison and the entomobryid Orchesella villosa. The F. octooculata mitochondrial genome generally conforms with those observed in other basal hexapod species and displays the plesiomorphic gene order observed for Pancrustacea. Mitogenomic data are useful to reconstruct a molecular phylogeny of major collembolan taxa. In spite of the limited number of species for which entire mitochondrial genomes are known, the coverage of many of the major lineages allows some preliminary conclusions concerning the relationships among families and suborders.